Direct observation of the formation and stabilization of metallic nanoparticles on carbon supports - Huang, Zhennan; Yao, Yonggang; Pang, Zhenqian; Yuan, Yifei; Li, Tangyuan; He, Kun; Hu, Xiaobing; Cheng, Jian; Yao, Wentao; Liu, Yuzi; Nie, Anmin; Sharifi-Asl, Soroosh; et al. (Nature communications, 2020)
Direct formation of ultra-small nanoparticles on carbon supports by rapid high temperature synthesis method offers new opportunities for scalable nanomanufacturing and the synthesis of stable multi-elemental nanoparticles. However, the underlying mechanisms affecting the dispersion and stability of nanoparticles on the supports during high temperature processing remain enigmatic. In this work, we report the observation of metallic nanoparticles formation and stabilization on carbon supports through in situ Joule heating method. We find that the formation of metallic nanoparticles is associated with the simultaneous phase transition of amorphous carbon to a highly defective turbostratic graphite (T-graphite). Molecular dynamic (MD) simulations suggest that the defective T-graphite provide numerous nucleation sites for the nanoparticles to form. Furthermore, the nanoparticles partially intercalate and take root on edge planes, leading to high binding energy on support. This interaction between nanoparticles and T-graphite substrate strengthens the anchoring and provides excellent thermal stability to the nanoparticles. These findings provide mechanistic understanding of rapid high temperature synthesis of metal nanoparticles on carbon supports and the origin of their stability. Metal nanoparticle-decorated carbon supports are vital for many applications, ranging from energy storage and catalysis to filtration and environmental remedies. Here, using real-time electron microscopy of a single carbon nanofiber during Joule heating, the authors report atomistic mechanisms responsible for nucleation and stabilization of nanoparticles on amorphous carbon supports.